Sophocarpine Protects Mice from ConA-Induced Hepatitis via Inhibition of the IFN-Gamma/STAT1 Pathway - Sang, Xiu-Xiu; Wang, Rui-Lin; Zhang, Cong-En; Liu, Shi-Jing; Shen, Hong-Hui; Guo, Yu-Ming; Zhang, Ya-Ming; Niu, Ming; Wang, Jia-Bo; Bai, Zhao-Fang; Xiao, Xiao-He (Frontiers in Pharmacology, 2017)
Abstract: Sophocarpine is the major pharmacologically active compound of the traditional Chinese herbal medicine Radix Sophorae Subprostratae which has been used in treating hepatitis for years in China. It has been demonstrated that Sophocarpine exerts an activity in immune modulation and significantly decreases the production of inflammatory cytokines. However, the protective effects of Sophocarpine in T cell-dependent immune hepatitis remained unknown. The aim of this study was to determine the protective effects and pharmacological mechanisms of Sophocarpine on Concanavalin A (ConA)-induced hepatitis, an experimental model of T cell-mediated liver injury. BALB/C mice were pretreated with Sophocarpine or Bicyclol for 5 consecutive days. Thirty minutes after the final administration, the mice were injected with 15 mg·kg-1 of ConA intravenously. The results indicated that pretreatment with Sophocarpine significantly ameliorated liver inflammation and injury as evidenced by both biochemical and histopathological observations. Moreover, in Sophocarpine-pretreated mice, liver messenger RNA expression levels of chemokines and adhesion molecules, such as Macrophage inflammatory protein-1α (MIP-1α), CXC chemokine ligand 10 (CXCL10) and Intercellular adhesion molecule-1 (ICAM-1), were markedly reduced. Further studies revealed that Sophocarpine significantly downregulated the expression of T-bet via inhibition of Signal transducers and activators of transcription1 (STAT1) activation and overexpression of Suppressor of cytokine signaling1 (SOCS1), inhibiting the activation of Th1 cells and the expression of Interferon-γ (IFN-γ). Altogether, these results suggest new opportunities to use Sophocarpine in the treatment of T cell-mediated liver disease. In summary, Sophocarpine could attenuate ConA-induced liver injury, and the protective effect of Sophocarpine was associated with its inhibition effect of pro-inflammatory cytokines, chemokines, and the IFN-γ/STAT1 signaling pathway.